High prevalence of cardiac dysfunction or overt heart failure in 71-year-old men: A 21-year follow-up of "The Study of men born in 1943". (May 2020) - Chen, Xiaojing; Thunström, Erik; Hansson, Per-Olof; Rosengren, Annika; Mandalenakis, Zacharias; Zhong, You; Ergatoudes, Constantinos; Caidahl, Kenneth; Fu, Michael
Background: Knowledge about long-term risk factors and the prevalence of heart failure stages in general population is limited. We aimed to study the prevalence of cardiac dysfunction and heart failure in 71-year-old men and potential risk factors in the past two decades. Design: This research was based on a randomized selected population study with longitudinal follow-up. Methods: A random sample of men born in 1943 in Gothenburg, Sweden were examined in 1993 (at 50 years of age) and re-examined 21 years later in 2014 (at 71 years of age). Cardiac dysfunction or heart failure was classified into four stages (A–D) according to American Heart Association/American College of Cardiology guidelines on heart failure. Results: Of the 798 men examined in 1993 (overall cohort), 535 (67%) were re-examined in 2014 (echo cohort). In the echo cohort 122 (23%) men had normal cardiac function, 135 (25%) were at stage A, 207 (39%) men were at stage B, 66 (12%) men were at stage C, and five (1%) men were at stage D. Multivariable logistic regression demonstrated that elevated body mass index at 50 years old was the only independent risk factor for developing heart failure/cardiac dysfunction during the subsequent 21 years. For each unit (1 kg/m 2 ) of increased body mass index, the odds ratio for stages C/D heart failure vs no heart failure/stage A increased by 1.20 (95% confidence interval, 1.11–1.31, p  < 0.001), after adjustment for smoking, sedentary life style, systolic blood pressure, diabetes, and hyperlipidemia. Conclusion: In a random sample of men at 71 years of age, half presented with either cardiac dysfunction or clinical heart failure. High body mass index was associated with an increased risk for developing cardiac dysfunction or heart failure over a 21-year period.